Fiction romanesque et histoire du féminisme : à propos de La Main gauche de la nuit - Justine Muller (ReS Futurae)
The thought esperiment of Ursula K. Le Guin when staging androgynous beings in The Left Hand of Darkness builds itself on the earlier feminist currents and announces a series of other currents that integrate, for the majority, Postmodern ideas that started to spread in the 60s. In doing so, her work is a reflection of the raising questions and claims that characterize the various waves that cross the history of feminism. Like any science-fiction work, Le Guin’s novel is at the crossroads of reality and fiction in that it allows a criticism of present times and a renewal of the genre as much as it anticipates certain feminist theories that appeared in the 70s, 80s and 90s.